1986
DOI: 10.1172/jci112386
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal antithrombin III with defective serine protease binding (antithrombin III "Denver").

Abstract: A hereditary (three family members) deficiency of antithrombin III (AT-III) in which AT-III antigen (AT-III ag) is normal in spite of low heparin cofactor and antithrombin activity is described. Plasma levels were: AT-III ag, 0.92-0.96 U/ml; AT-III heparin cofactor activity, 0.54-0.62 U/ml; progressive antithrombin activity index, 0.13-0.18; anti-Xa activity, 0.50-0.56 U/ml. Plasma crossed immunoelectrophoresis (CIE) patterns performed with and without added heparin were normal, but serum CIE revealed a decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Of the remaining 37 studies, 24 reported on type 1 antithrombin III deficiency (1,40-62), 13 on type 2a or b antithrombin III deficiency (63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75), and none on type 2c antithrombin III deficiency. The prevalence of a history of venous thrombotic disease was statistically significantly higher (p < 0.001) in type 1-deficient family members (44%; 85/192) than in nondeficient family members (2%; 6/248) (estimated common odds ratio, 13.7; 95% confidence interval, 8.4-22.5).…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining 37 studies, 24 reported on type 1 antithrombin III deficiency (1,40-62), 13 on type 2a or b antithrombin III deficiency (63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75), and none on type 2c antithrombin III deficiency. The prevalence of a history of venous thrombotic disease was statistically significantly higher (p < 0.001) in type 1-deficient family members (44%; 85/192) than in nondeficient family members (2%; 6/248) (estimated common odds ratio, 13.7; 95% confidence interval, 8.4-22.5).…”
Section: Resultsmentioning
confidence: 99%
“…27 All of them have slightly different molecular structures, which give a diminished activity but have a normal concentration. The type 2b deficiencies have an isolated diminution of the serpin activity and were described as AT Aalborg, 28 Vicenza, 29 Hvidove, 30 Denver, 31 Charleville, 32 Milano 2, 33 Pescara, 34 Hamilton, 35 and Avranches. 36 AT 2c abnormalities are characterized by isolated alterations at the heparin binding site.…”
Section: Deficiency Of Atmentioning
confidence: 99%
“…The presence of two distinct binding sites for thrombin and for heparin was previously reported in normal AT III (2); accordingly, AT III pathological molecular variants frequently show a defective binding to serine proteases (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) or to heparin (I5-ZI), whereas an impairment of both functional activities was found rarely (22)(23)(24).…”
mentioning
confidence: 81%